EXACT VALUES OF THE ATES-DOMINATION NUMBER OF SOME SPECIALIZED TYPES OF GRAPHS. Issue 1 (May 2021) - Anuthiya, S.; Mahadevan, G.
Abstract: Recently, G. Mahadevan et.al. proposed the idea of ATES domination number of a graph. In [6] A set S ⊆ V is said to be At most twin extendable separated dominating set, if for every vertex 1 ≤ | N ( V ) ∩ S | ≤ 2, v ∊ V − S and < V − S > is a perfect matching. The minimum cardinality taken over all At most twin extendable separated dominating sets is called At most twin extendable separated domination number of a graph and it is denoted by ATES (G). In this article, we analyze this number for some specializes types of graphs.